Correlation between quality of life, depression, satisfaction and functionality of older people with HIV - Kydja Milene Souza Torres de Araújo; Suelane Renata de Andrade Silva; Daniela de Aquino Freire; Márcia Carréra Campos Leal; Ana Paula de Oliveira Marques; Rosilene Santos Baptista; Antônia Leda Oliveira Silva (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: To analyze the correlation between the quality of life, depression, life satisfaction, and functional capacity in elderly people living with the Human Immunodeficiency Virus (HIV). Methods: A cross-sectional study developed in reference hospitals for treatment and follow-up of people with HIV. 241 elderly people participated by applying a questionnaire containing sociodemographic variables, the HIV/AIDS target quality of Life, the Barthel Index, the Life Satisfaction Scale, and the abbreviated version with 15 items of the Yesavage Geriatric Depression Scale. Results: The analyses showed an inverse correlation between the dimensions of the HAT-Qol with depression, a positive correlation in the domain satisfaction with life, and statistically significant, but weak, with functionality. Conclusion: Depression impairs quality of life in all dimensions, while life satisfaction influences this aspect more positively than functional capacity. Descriptors: Quality of Life; Depression; Personal Satisfaction; Aged; HIV.